Growth imperatives as a conflict between efficiency and justice - Andreas Siemoneit (Carl von Ossietzky University Oldenburg; ZBW - Leibniz Information Centre for Economics, 2023)
Economic growth (i.e., GDP increase) is a key concept in economics and politics. It is regarded as indispensable for sustainably securing an adequate standard of living and as an important prerequisite for solving (or at least mitigating) social distribution problems. However, the ecological effects of economic growth are now catastrophic, and the social benefits of further growth at a high level are controversial. For a long time, therefore, both activists and social scientists have debated the question of whether individual or collective decisions for economic growth are truly voluntary or whether coercive mechanisms of some kind make economic growth inevitable. In this discourse, virtually all concepts are “essentially contested” and many terms are not consistently defined. The aim of this interdisciplinary theoretical work is a fundamental investigation and clarification of terminology and conceptual approaches and subsequently a substantiated answer to the question whether growth imperatives exist or not, and if so, what the social and/or economic mechanisms are. Much of the research work was done in collaboration with Oliver Richters (see Preface). We structured the debate on growth imperatives along two dimensions: (a) degree of coerciveness between free will and coercion, and (b) agents affected. With carefully derived micro level definitions of “social coercion” and “growth imperative,” we discussed several mechanisms suspected to make growth necessary for firms, households, and nation states. We identified technological innovations as a systematic necessity to net invest, trapping firms and households in a positive feedback loop to increase efficiency (throughout this work, the plain term “efficiency” is used in the sense of optimal individual effort, not in the sense of the Pareto efficiency of Economics where it means the optimal distribution of net benefits). Resource-intensive technology is economically attractive because of a subtle violation of the so-called meritocratic principle. The dilemma between “technological unemployment” and the social necessity of high employment explains why nation states must foster economic growth. All other mechanisms discussed deemed us to be implausible under our definitions. Three topics required more detailed investigation due to their discursive history and substantive importance: (1) It is disputed whether a growth imperative is located within the current monetary system. To examine the claim that compound interest compels economies to grow, we presented five post-Keynesian Stock-Flow-Consistent models and showed how to perform a stability analysis in the parameter space. The other claim that retained profits from the interest revenues of banks create an imperative is based on circuitist models that we considered refutable. Their accounting is inconsistent, and a modeling assumption central for a growth imperative is not underpinned theoretically. (2) A growth imperative only for firms who then encounter consumers unwilling to consume would quickly die out. But up to now, unwillingness to consume is a rarity, and the reasons why consumers are buying more and more are disputed. I explore the thesis that both firms and consumers frequently acquire goods that increase their efficiency (productivity). For firms, efficiency is accepted as a main investment motive, but for consumers it is usually framed as convenience, ease, or comfort. Via social diffusion processes certain consumer goods that can save time and costs are transformed from a welcome expansion of possibilities into a social imperative whose noncompliance over time also has economic drawbacks. This leads to similar positive feedback-loops for consumers and firms, contributing to a vicious circle of economic growth. (3) The social norm Meritocratic Principle is crucial for a detailed understanding of how the growth imperative works but its actual significance for distributive justice is disputed. Three principles of distributive justice occupy center stage in the debate: merit (aka equity or desert), need, and equality. Yet their relation remains diffuse, and current theory does not inform political practice. I argue that from an evolutionary point of view, the primary principle of justice is reciprocity in social exchange (what corresponds to merit). Need and equality are auxiliary principles when merit is not effective, not efficient, or not communicable. The reciprocal social norm Meritocratic Principle can be implemented, and its controversy avoided, by concentrating on “non-merit,” i.e., institutionally draining the wellsprings of undeserved incomes (economic rents). Avoiding or taxing away economic rents is an effective implementation of justice in market economies.
Keywords: O33; D63; 330; Growth imperative; Biological efficiency; Justice